CLARISA Institution request protocol - Almanzar, Manuel; Tobon, Hector; Pérez, Diego (CGIAR Level Agricultural Results Interoperable System Architecture, 2021)
This short document briefly describes the protocol used by CLARISA to receive requests, from other Management Information Systems, to add new institutions that are not part of the current list